2016
DOI: 10.1080/2162402x.2016.1238539
|View full text |Cite
|
Sign up to set email alerts
|

Rapid tumor regression in an Asian lung cancer patient following personalized neo-epitope peptide vaccination

Abstract: Personalized immunotherapy targeting tumor-specific mutations represents a highly promising approach to cancer treatment. Here, we describe an Asian lung squamous cell carcinoma patient demonstrating frank disease progression following chemotherapy and EGFR inhibitor treatment. Based on tumor mutational profiling and HLA typing, a saline-based multi-epitope peptide vaccine was designed and administered along with topical imiquimod as an adjuvant. Weekly neo-epitope peptide vaccination was followed by a rapid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…NetMHCpan (http://www.cbs.dtu.dk/services/NetMHCpan/) is widely used for peptide prediction (38,(42)(43)(44)(45)(46). Based on previous knowledge, peptide prediction using NetMHCpan showed that the P motif of HLA-A * 30:01-binding peptides was biased toward both A1 supertype-preferred residues (Ile and Leu), and A3 supertype-preferred residues (Arg and Lys) ( Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NetMHCpan (http://www.cbs.dtu.dk/services/NetMHCpan/) is widely used for peptide prediction (38,(42)(43)(44)(45)(46). Based on previous knowledge, peptide prediction using NetMHCpan showed that the P motif of HLA-A * 30:01-binding peptides was biased toward both A1 supertype-preferred residues (Ile and Leu), and A3 supertype-preferred residues (Arg and Lys) ( Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
“…Screening of immunogenic peptides which are presented by specific MHC I molecules is crucial for the development of vaccines for infection diseases or cancer immunotherapy and for T-cell immune response evaluation (45)(46)(47)(48)(49)(50)(51). Recently, several pre-clinical and clinical studies have shown that vaccines targeting predicted personal tumor neoantigens are feasibility, safety, and immunogenicity (45,50,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al designed a saline-based multi-epitope peptide vaccine and demonstrated rapid tumour shrinkage of multiple lung tumour nodules in a lung cancer patient following administration 63 . However, eight weeks following the initiation of vaccination, the patient died from complications due to the progression of liver metastases.…”
Section: Future Perspectives Of Neoantigen Vaccinesmentioning
confidence: 99%
“…Naturally occurring tumor infiltrating lymphocytes (TILs) are mostly directed towards neoantigens, their frequency correlates to the tumor mutational burden and associate with increased survival [ 5 8 ]. Therapeutic cancer vaccines based on mutated neoantigens are currently evaluated in clinical trials showing significant prolonged patients’ survival, including also synthetic long peptide vaccines which are capable of inducing both CD8+ and CD4+ neoantigen-specific T-cell responses [ 9 12 ]. Moreover, clinical benefit of melanoma and lung cancer patients treated with checkpoint inhibitors (anti-CTLA-4 and PD-1) has been found to correlate not only with pre-existing T-cell infiltration and PD-L1 expression in tumors [ 13 ], but also with the mutational burden of treated tumors [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%